2010
DOI: 10.1038/ncomms1046
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying beneficial plant–fungus interactions in mycorrhizal symbiosis

Abstract: Mycorrhizal fungi are a heterogeneous group of diverse fungal taxa, associated with the roots of over 90 % of all plant species. Recently, state-of-the-art molecular and genetic tools, coupled to high-throughput sequencing and advanced microscopy, have led to the genome and transcriptome analysis of several symbionts. Signalling pathways between plants and fungi have now been described and the identifi cation of several novel nutrient transporters has revealed some of the cellular processes that underlie symbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
675
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 1,082 publications
(691 citation statements)
references
References 97 publications
(125 reference statements)
8
675
0
8
Order By: Relevance
“…Both partners gain an advantage from the symbiosis; the fungus supplies the plant with mineral nutrients (mainly phosphate) increasing, plant biomass and improving its resistance to pathogens and environmental stresses including oxidative stress conditions (Garcia-Sànchez et al 2014), while the host provides organic carbon to the fungus (Bonfante and Genre 2010). Plant and fungal nutrition is thus mutually improved (Kiers et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Both partners gain an advantage from the symbiosis; the fungus supplies the plant with mineral nutrients (mainly phosphate) increasing, plant biomass and improving its resistance to pathogens and environmental stresses including oxidative stress conditions (Garcia-Sànchez et al 2014), while the host provides organic carbon to the fungus (Bonfante and Genre 2010). Plant and fungal nutrition is thus mutually improved (Kiers et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase Pi uptake, plants have evolved different strategies, such as the enhanced growth of lateral roots and root hairs, and/or the solubilization of soil Pi by means of organic acid and phosphatase secretion: all these processes are probably orchestrated by a systemic signalling that is triggered during Pi starvation (Doener 2008;Lambers et al 2011;Péret et al 2011) and involves specific gene expression regulators, as has been demonstrated in Arabidopsis (Pérez Torres et al 2009). Another widespread and evolutionary ancient strategy is the establishment of arbuscular mycorrhizal (AM) symbiosis which involves the majority of land plants and fungi belonging to the Glomeromycota phylum (Parniske 2008;Bonfante and Genre 2010). AM fungi ensure that their host plants have an efficient supply of mineral nutrients, particularly P and nitrogen (Allen and Shachar-Hill 2009;Tian et al 2010;.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, diverse regulatory signals, including plant-derived chemicals, are present in the soil to translate a wealth of information that ultimately leads to growth responses of the interacting partners. An important interaction, which proved crucial for land plant evolution, is the symbiosis with mycorrhizal fungi belonging to the Glomeromycota (Bonfante and Genre 2010). These fungi are obligate heterotrophs that supply the plant with nutrients [mainly phosphate (Pi) and nitrogen (N)] and, in return, the plant delivers photosynthetic assimilates to the fungi.…”
Section: Introductionmentioning
confidence: 99%